Design and Implementation of New Future Television Cloud Computing (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
A design and implementation of new future TV Cloud Computing (ClComp)Â  for international systems integration and bridging the gap between linear broadcast, information technology and Internet Protocol of television and mobile television is presented to help Authorized Groups (AuthGs) reach and engage audiences on any television screen. . The cloud design is applied to the Egyptian Radio and Television Union (ERTU). The applications, security, efficiency, flexibility, greater agility, less expenditure and to overcome geographic limitations which are the solution of the cloud are introduced to compete in a global market. The design and evaluation steps are addressed to insure the reliability and compatibility of cloud to the desired targets. A software package for audio watermarking has been presented as an example for its application to ensure protection, in case of saving, and security, in case of transmission of the media through the proposed cloud. The package contains many visual tests such as probability, spectrum, power and scatter diagrams to enable user to quickly investigate the content. All this application was done to suit the webâ€“based where many departments can get benefit from anywhere and anytime according to department request and cloud polices.